Race and ethnicity determine serum insulin and C-peptide concentrations and hepatic insulin extraction and insulin clearance: comparative studies of three populations of West African ancestry and white Americans - Osei, K.; Schuster, D.P.; Owusu, S.K.; Amoah, A.G. (Metabolism, 1997)
We examined the importance of ethnicity in terms of β-cell secretion and hepatic insulin extraction (HIE) and insulin clearance (IC) to peripheral insulin levels before and after stimulation in three populations of West African ancestry, namely African-Americans, Ghanaian immigrants, and native Ghanaians living in diverse environments, and white Americans. Following 10 to 12 hours of overnight fasting, each subject ingested a 75-g oral glucose load. Blood samples for determination of serum glucose, insulin, and C- peptide were obtained at baseline and after the oral glucose load at 30- minute intervals for 240 minutes. Basal HIE and IC were calculated as the molar ratios of C-peptide and insulin concentrations at basal steady state, and postprandial values as molar ratios of the incremental integrated C- peptide and insulin areas. Clinical characteristics of the patients were not significantly different among the four groups. During the fasting and postprandial state, serum glucose levels were not significantly different among the four groups. Surprisingly, the mean fasting insulin concentration was significantly greater in native Ghanaians (21.19 ± 0.93 μU/mL, P < .05) than in African-Americans (11.90 ± 1.02 μU/ML), Ghanaian immigrants (8.14 ± 0.96 μU/mL), and white Americans (7.03 ± 0.78 μU/mL). Following the oral glucose load, the mean serum peak and incremental integrated areas of insulin were significantly (P < .05) greater in native Ghanaians, African- Americans, and Ghanaian immigrants compared with white Americans. In contrast, there were no significant differences in postprandial serum insulin responses among the three groups of West African ancestry, irrespective of country of origin or residence. Despite the higher insulin concentrations in blacks of West African ancestry compared with whites, the corresponding basal and postprandial serum C-peptide levels were not significantly different among the four groups. Mean basal and postprandial HIE and IC were significantly (P < .05 to .01) reduced (25% to 52%) in the three populations of West African ancestry compared with the white Americans, but these values were not significantly different among the West African descendants. When comparing metabolic responses in obese (body mass index [BMI] > 27 kg/m2) and non-obese (BMI < 27 kg/m2) native Ghanaians, we found no significant differences in fasting insulin, C-peptide, and basal HIE or IC. Also, there were no significant relations between fasting and postprandial serum insulin, obesity indices, and HIE and IC in any of the groups. In summary, our study demonstrates that glucose-tolerant native Ghanaians, Ghanaian immigrants, and African-Americans of West African ancestry manifest hyperinsulinemia and a decreased HIE and IC compared with white Americans. We conclude that race and ethnicity may be the major determinants of the mechanism(s) of β-cell secretion, insulin action, and peripheral insulin levels and HIE or IC in humans. We speculate that the lower HIE and IC in blacks of West African descent appears to be a highly conserved metabolic trait irrespective of the country of residence.
Keywords: Adult; African Continental Ancestry Group; Aging; Body Height; Body Mass Index; Body Weight; C-Peptide; European Continental Ancestry Group; Female; Ghana; Glucose; Humans; Insulin; Liver; Male; Obesity; United States